المنهج التفسيري لكليات الأساليب: دراسة تحليلية في جهود المفسرين وتأثيرها على فهم النص القرآني: The Interpretative Methodology of Universal Styles: An Analytical Study on the Efforts of Exegetes and Their Impact on Understanding the Quranic Text - Al Farabi, Fahmi Akhyar; Farhan Afif Al-Kindi (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
إن علماء التفسير يهتم بعلوم في القرآن الكريم خصوصا في علم اللغة. إحدى الدراسة في علم اللغة هي دراسة عن كليات والأساليب. وكليات الأساليب القرآنية هي نوع هام عظيم من أنواع الكليات. هدف هذه الدراسة إلى التوضيح والإجابة عن قواعد كليات الأساليب عند المفسرين في القرآن الكريم. نوعية هذه الدراسة هي الدراسة المكتبية للحصول على حقائق المعنى الدلالي قواعد كليات الأساليب عند المفسرين باستخدام المنهج الوصفي والتحليلي لحل المشكلات الدراسية. واستندت طريقة جمع بياناتها بالاطلاع والقراءة المتكررة على تلك المصادر الذي له علاقة به. وتواصلت نتائج هذا البحث هو أن موضوع الكليات قديم النشأة أصيل الظهور ونال كثيرٌ من أئمة التفسير عناية الدارسين ولكن بدا أنهم لم يؤلوا جانب الكليات خصوصا كليات الأساليب عند أولئك المفسرين. فكان لزاماً لهذه، ظهور أولئك المفسرين وقواعد، ومن أبرزهم: قاعدة الرازي في سورة البقرة الآية ٩٨ ، قاعدة ابن القيم في سورة المائدة الآية ٩٨، قاعدة الشنقيطي في سورة آل عمران الآية ۷، سورة النمل الآية ٦٥، سورة الأعراف الآية ۱۸۷، سورة القصص الآية ۸۸ ، وقاعدة السيوطي في سورة الكهف: 49-54 والإسراء 71-89. Qur'anic exegetes have paid close attention to the sciences within the Qur'an, particularly linguistic sciences. One of the key areas of linguistic study is the examination of kulliyyāt (universal principles) and asālīb (stylistic methods). Kulliyyāt al-asālīb al-Qur’āniyyah constitutes a significant and essential category within the broader framework of kulliyyāt. This study aims to clarify and analyze the principles of kulliyyāt al-asālīb as understood by Qur'anic exegetes. The research adopts a library-based methodology to uncover facts regarding the semantic principles of kulliyyāt al-asālīb, utilizing a descriptive and analytical approach to address academic inquiries. The data collection method involves repeated reviews and thorough readings of relevant sources. The study concludes that the discourse on kulliyyāt dates back to early periods and has been a subject of scholarly attention among leading Qur'anic exegetes. However, it appears that less focus has been given to kulliyyāt, particularly kulliyyāt al-asālīb, in their interpretations. The research highlights key exegetical principles developed by prominent scholars, including Al-Rāzī’s principle in Surah Al-Baqarah (2:98), Ibn al-Qayyim’s principle in Surah Al-Mā’idah (5:98), Al-Shanqīṭī’s principles in Surah Āl ‘Imrān (3:7), Surah Al-Naml (27:65), Surah Al-A‘rāf (7:187), and Surah Al-Qaṣaṣ (28:88), as well as Al-Suyūṭī’s principles in Surah Al-Kahf (18:49-54) and Surah Al-Isrā’ (17:71-89). Contribution: This study contributes to Qur'anic exegesis by highlighting the overlooked role of universal styles (kulliyyāt al-asālīb) in interpretation, analyzing key exegetes, and offering a structured framework for future linguistic and exegetical research.